The Students Challenges in Learning Difthong - Zulio Diva Ananta; Wanda Riani Hasibuan; Yani Lubis (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research examines students’ difficulties in conveying English diphthongs, especially closing and middle diphthongs. This study was conducted qualitatively with a phenomenological approach through interviews with students in the first semester of the English Language Education Study Program at the State Islamic University of North Sumatra. The research results show that the influence of mother tongue is very significant on the accuracy of different pronunciations. The main factors include difficult vowel transitions, differences in phonological systems between Indonesian and English, and the substitution of diphthongs for pure vowels. Closing diphthongs such as /eɪ/, /aɪ/, and /oʊ/ were found to be more difficult to pronounce than middle diphthongs because they require faster and more accurate vowel movements. Apart from that, internal factors such as lack of self-confidence also contribute to pronunciation errors. This study suggests the use of intensive practice, learning technology, and immediate feedback to improve diphthong pronunciation accuracy.